Pengembangan Bahan Ajar Digital Flipbook Berorientasi Problem Based Learning untuk Meningkatkan Pengetahuan Faktual dan Konseptual pada Materi Bunyi di Kelas 4 SDN 104 Kota Bengkulu - Elva Susanti; Irwan Koto; Endang Widi Winarni (Jurnal Kajian Pendidikan Dasar, 2024)
This research aims to develop a PBL (Problem-Based Learning) oriented flipbook in improving factual and conceptual knowledge. The problem of this research is the low learning outcomes of students on factual and conceptual knowledge. The purpose of this study was to design and test the effectiveness of PBL-oriented flipbooks in improving students' factual and conceptual knowledge. This research uses a 4D development approach (Define, Design, Develop, Disseminate). The Define stage involves identifying the needs, objectives, and context of the study. The Design stage involves designing the initial design of the product or model to be developed. The Develop stage involves the implementation and development of the product or model. The Disseminate stage involves disseminating and evaluating the product or model to relevant stakeholders. The results of flipbook development research show that PBL-oriented flipbook digital teaching materials are feasible to use. Student response was positive, with 91% of students meeting the criteria for either. This teaching material has also proven effective in improving factual and conceptual knowledge, as shown by the average N-gain score in the experimental class of 0.63 (medium category), while in the control class it was only 0.20 (low category). The conclusion of flipbook development research shows that PBL-oriented flipbook digital teaching materials are worth using. Student response is positive, and effective for improving factual and conceptual knowledge.